2019
DOI: 10.1542/hpeds.2018-0233
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Respiratory Viral Testing in Hospitalized Children: A Meta-analysis

Abstract: CONTEXT: Respiratory virus (RV) detection tests are commonly used in hospitalized children to diagnose viral acute respiratory infection (ARI), but their clinical utility is uncertain. OBJECTIVES: To systematically review and meta-analyze the impact of RV test results on antibiotic consumption, ancillary testing, hospital length of stay, and antiviral use in children hospitalized with severe ARI. DATA SOURCES: Seven medical literature databases from 1985 through January 2018 were analyzed. STUDY SELECTION: Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…20 However, single-center studies and a systematic review and meta-analysis have demonstrated discordant results for the benefit of viral testing on these outcomes in children hospitalized with respiratory illnesses. [21][22][23][24] In our analysis, the average length of stay and average duration of antibiotics during hospitalization were both ~2 days, and viral testing was not associated with these outcomes at the hospital level.…”
Section: Hospital-level Testing and Outcomesmentioning
confidence: 99%
“…20 However, single-center studies and a systematic review and meta-analysis have demonstrated discordant results for the benefit of viral testing on these outcomes in children hospitalized with respiratory illnesses. [21][22][23][24] In our analysis, the average length of stay and average duration of antibiotics during hospitalization were both ~2 days, and viral testing was not associated with these outcomes at the hospital level.…”
Section: Hospital-level Testing and Outcomesmentioning
confidence: 99%
“… 4 , 10 , 11 However, the impact of viral diagnostic testing on antibiotic administration for children with ARI remains unclear due to conflicting results, with some studies reporting that viral diagnostics are associated with lower antibiotic use, while others report no impact. 12 , 13 Likewise, studies examining viral testing and antibiotic prescribing and administration practices in both EDs and inpatient settings are limited. Therefore, in this prospective study, we aimed to evaluate the association of (1) provider-ordered viral testing and antibiotic treatment, and (2) provider-ordered viral test result (ie, positive, negative) and antibiotic treatment among children presenting to an ED or hospitalized with an ARI at major tertiary care children’s hospital in Nashville, Tennessee.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, viral ARIs are often identified with point-of-care antigen tests or novel molecular diagnostic assays, but, these tests can be costly and not readily accessible to many healthcare settings worldwide 6–8. This challenge requires clinicians to infer ARI aetiologies based on clinical features, which is prone to diagnostic uncertainty as viral and bacterial ARI symptoms overlap 9 10. In an attempt to increase diagnostic certainty, researchers developed several prediction models to facilitate diagnosis of viral ARIs.…”
Section: Introductionmentioning
confidence: 99%